2019
DOI: 10.14309/01.ajg.0000593012.88666.3e
|View full text |Cite
|
Sign up to set email alerts
|

869 A Comparison of ERCP Outcomes Between High Volume and Low Volume Centers

Abstract: INTRODUCTION: Endoscopic Retrograde Cholangiopancreatography (ERCP) is a commonly performed procedure for simultaneous diagnosis and treatment of biliary disease, which has several potential post-procedural complications. Few studies have addressed the association between hospital ERCP volume and post procedural complications. This study aims to examine the difference in the rate of post ERCP complications between high and low volume centers. METHODS: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The incidence of PEP in this study is higher than prior studies (14), likely due to a combination of a high proportion of cases with a pancreatic indication (53%) and a high proportion of ASGE complexity scores of 3 and 4 (57%) (15). Past studies have suggested that a higher rate of complications are seen in procedures with higher complexity (16). Additionally, a prior retrospective review demonstrated high rates of PEP in pediatric patients who underwent PD cannulation, as high as 25% (17).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PEP in this study is higher than prior studies (14), likely due to a combination of a high proportion of cases with a pancreatic indication (53%) and a high proportion of ASGE complexity scores of 3 and 4 (57%) (15). Past studies have suggested that a higher rate of complications are seen in procedures with higher complexity (16). Additionally, a prior retrospective review demonstrated high rates of PEP in pediatric patients who underwent PD cannulation, as high as 25% (17).…”
Section: Discussionmentioning
confidence: 99%
“…Data synthesis was obtained by direct meta-analyses using random-effects model. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31…”
mentioning
confidence: 99%